Alliance Building to Create Change: The Women's Movement and the 1982 CUPW Strike - Nichols, Leslie J. (Just Labour, 2012)
Social movements are significant to change mainstream ideologies and values over what is seen to be critical for society. The women’s movement helped to change ideas about women and their roles in society . One significant change, for more universal maternity, only occurred through the alliance with CUPW. This paper will illustrate that the alliance between the women’s movement and CUPW was significant to change public opinion and help to gain paid maternity leave for the majority of working women in Canada. In sum, the power these two groups generated in alliance produced one of the most important social benefits we currently enjoy as Canadian citizens. As a result, alliances are powerful and should be used to further any movement to towards equality.